ANALYSIS OF BRONCHIAL ASTHMA TREATMENT IN CHILDREN (The New Uzbekistan Journal of Medicine, 2025)
This article is devoted to the treatment of bronchial asthma in children. Bronchial asthma is a disease characterized by chronic inflammation and obstruction of the respiratory tract, which is widespread in children. The article considers the causes, symptoms, diagnostics, treatment methods and current issues of asthma prevention. Pharmacological methods for the effective treatment of children with bronchial asthma, special treatment methods in cases of allergy-related asthma and preventive measures are described. This article provides important information for developing practical approaches to managing and controlling the disease in children with asthma.